2004
DOI: 10.1017/s0031182004004822
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics ofWuchereria bancroftiinfection: a model-based analysis of longitudinal data from Pondicherry, India

Abstract: This paper presents a model-based analysis of longitudinal data describing the impact of integrated vector management on the intensity of Wuchereria bancrofti infection in Pondicherry, India. The aims of this analysis were (1) to gain insight into the dynamics of infection, with emphasis on the possible role of immunity, and (2) to develop a model that can be used to predict the effects of control. Using the LYMFASIM computer simulation program, two models with different types of immunity (anti-L3 larvae or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 65 publications
2
85
0
Order By: Relevance
“…The life span of the adult worm was 10.2 years without chemotherapy and it was reduced to 5.3 years following diethyl-carbamazine therapy (Vanamail et al 1990). Another study reports that the adult parasites can live as long as 10 years in humans (Subramanian et al 2004) and samples from older age class would show positive reaction making it difficult to Table 1 Positivity and negativity of samples tested with different quantity of serum for filarial specific antigens by Og4C3 antigen assay (?ve and TG 8) 2.209 (?ve and TG 8) decide whether the infection occurred during the intervention period or earlier. Therefore, it is ideal to screen children who were born after the introduction of MDA to verify whether transmission was interrupted or not.…”
Section: Discussionmentioning
confidence: 99%
“…The life span of the adult worm was 10.2 years without chemotherapy and it was reduced to 5.3 years following diethyl-carbamazine therapy (Vanamail et al 1990). Another study reports that the adult parasites can live as long as 10 years in humans (Subramanian et al 2004) and samples from older age class would show positive reaction making it difficult to Table 1 Positivity and negativity of samples tested with different quantity of serum for filarial specific antigens by Og4C3 antigen assay (?ve and TG 8) 2.209 (?ve and TG 8) decide whether the infection occurred during the intervention period or earlier. Therefore, it is ideal to screen children who were born after the introduction of MDA to verify whether transmission was interrupted or not.…”
Section: Discussionmentioning
confidence: 99%
“…The study therefore confirmed that the previously observed static infection pattern at the individual level continued to persist for more than three decades. Because the mean lifespan of adult W. bancrofti worms in the human host has been estimated to about 10 years, 26 the static infection pattern indicates that re-infection commonly occurred in the study population, and that once individuals acquired infection they had a high risk of being re-infected, and thus of remaining infected for long periods-maybe for their entire life.…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable observation that W. bancrofti, B. malayi, and O. volvulus harbor endosymbiotic Wolbachia bacteria (4 -6) has raised the possibility that infected individuals respond to these organisms in addition to nematode ligands and that Wolbachia can initiate or promote inflammation (7)(8)(9)(10)(11)(12). Despite remarkable longevity in the human host (13), adult filarial worms themselves are not strong inducers of inflammation (3,14). Wolbachia bacteria are in the family Rickettsiacea and are obligatory intracellular bacteria that infect a wide variety of invertebrates, in which they have an important role in sex determination and speciation (15).…”
mentioning
confidence: 99%